Media treatment of sports corruption issues in the Algerian written press Analytical study of the sample for the Scorer newspaper - as a model – - affane, Sounia affane (sports creativity, 2025)
Study summary: This study aims to know the nature of the media treatment of sports corruption issues in the Algerian written press, as well as to clarify the interest of Al-Haddaf newspaper as a model for our study of sports corruption issues in Algeria, as well as to identify the role that the written press plays in dealing with corruption in the sports field. To achieve the objectives of this study, we used the sample survey approach, and our study sample was chosen by the systematic random method, and to determine the size of the study sample, we adopted the Stemple study where the sample size of our study was estimated at 12 individuals, and we used the content analysis form as a tool for the study after we defined the units of analysis and Its categories, and since our study is analytical, we treated them statistically by calculating frequencies and percentages. One of the most important findings of our findings is that the majority of the number of Al-Scorer newspaper (study sample) included a set of sports corruption cases, the most important of which are disputes between officials and non-payment of players' dues, as the parties to whom this corruption is attributed are mostly officials in the sports sector and referees, as it included these The numbers are types of sports corruption, on top of which is administrative corruption, followed by moral and financial corruption.